Effects of a mental health promotion intervention on mental health of Iranian female adolescents: a school-based study - Haleh Heizomi; Hamid Allahverdipour; Mohammad Asghari Jafarabadi; Devender Bhalla; Haidar Nadrian (BMC, 2020)
Abstract Background Poor mental health is common among adolescents. Given the increasing burden of poor mental health among adolescents in developing countries, it seems necessary to identify the effective interventions. The main purpose of this study was to investigate the effects of a school-based mental health promotion program (SMHPP) on mental health parameters among female adolescents in Tabriz, Iran. Method In this experimental study, a random sample of female high-school students of grade nine was recruited. The subjects were then randomly allocated to intervention (n = 145) and control (n = 139) groups. The three-stage SMHPP was designed based on the shortages and unmet needs of the students as reported in the pretest stage. All subjects in the intervention group were provided with a stress management skill training program of six sessions using McNamara Model. Coincided with making environmental changes, a joyful intervention program was carried out. After 2 months, post-test data were collected. Results A total of 284 students completed their participation in the study. The groups did not differ in none of socio-demographic characteristics and mental health parameters, at baseline. The number of subjects reporting medium-level of happiness was increased by 32.6% among intervention group. Moreover, upon sign test and pre-post comparison, the group-wise distribution changed between the intervention and control groups for the parameters of life satisfaction (p ≤ 0.001) and psychological well-being (p ≤ 0.01). Conclusion The implementation of SMHPP as a low-cost, needs-based and multifaceted program, showed promise in promoting adolescents' mental health, particularly in the parameters of happiness, life satisfaction and psychological well-being. This was an important evidence for the development and implementation of interventions and policies in the field of mental health promotion among adolescents. Our work provided means for reducing burden of poor mental health among adolescents in a non-western cultural context. Further larger studies are required to evaluate the effectiveness of such school-based mental health promotion interventions in students.